« Faire éclater le canon, arriver à un discours commun sur la littérature. » - Vicky Gauthier; Camille Islert; Martine Reid (Glad!)
The interview reproduced here was held on July 8, 2021 online. It first discusses the career of Professor Martine Reid, in order to explore heritages and constellations in connection with her own practice as a teacher and researcher in literature. Secondly, the notion of constellation is linked to the literary history of women, in order to discuss its relevance, and above all to evoke the particular (re)constitution of these networks and lineages that we still struggle to integrate permanently into a general narrative of literature.